1988
DOI: 10.1007/bf01311025
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic analysis of West Nile virus strains using monoclonal antibodies

Abstract: Seventeen monoclonal antibodies (MAbs) were prepared against the flavivirus West Nile strain H442. While the majority of these were specific for the major envelope protein, MAbs directed against the NS1 and ns4a nonstructural proteins were also identified. The MAbs were tested by indirect immunofluorescence against 16 southern African West Nile (WN) isolates, representative strains from the two main WN antigenic groups and several viruses from other flavivirus complexes. The MAb reactivities ranged from WN str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…The method for production and maintenance of monoclonal antibodies was based on that as described by Besselaar and Blackburn [3]. Positive clones were selected by testing the supernatants of the hybridoma cultures for antibody excretion using an ELISA with purified glycoprotein as the capture antigen.…”
Section: Monoclonal Antibody' Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…The method for production and maintenance of monoclonal antibodies was based on that as described by Besselaar and Blackburn [3]. Positive clones were selected by testing the supernatants of the hybridoma cultures for antibody excretion using an ELISA with purified glycoprotein as the capture antigen.…”
Section: Monoclonal Antibody' Productionmentioning
confidence: 99%
“…1000 Ci.mmol; Amersham Int., U.K.) for 4-20 h post-infection at 37 °C. The cells were washed with cold PBS, lysed with NP-40 buffer [3] and made 0.1% (w/v) with respect to SDS. The lysates were disrupted with a probe sonicator, clarified by centrifugation at 18000 g for 30 min and the supernatants used for MAb immunoprecipitation.…”
Section: Radioimmune Precipitation Assay ( Ripa )mentioning
confidence: 99%
See 1 more Smart Citation
“…Antigenic profiles of each isolate were compared by using a panel of anti-KUN monoclonal antibodies (MAbs) (26,27) and anti-WN MAbs (28,29) in ELISA as described (26). All MAbs were produced to the E protein except for 3.1112G, which was specific for the NS1 protein.…”
Section: Enzyme-linked Immunosorbent Assay (Elisa)mentioning
confidence: 99%
“…Thus, Hammam et al (1965) found that Indian and African WN virus isolates have different haemagglutination inhibition kinetics. Studies of cDNA\RNA heteroduplex restriction profiles and\or reactivity toward monoclonal antibodies (Besselaar & Blackburn, 1988 ;Mathiot et al, 1990) have identified several WN virus variants. More recently, Porter et al (1993) sequenced NS3 protein gene fragments of seven African and one Indian strains and defined three categories on the basis of nucleotide sequence similarity.…”
mentioning
confidence: 99%